Господарсько-корисні ознаки швіцьких корів ейрисомного та лептосомного типів конституції - Черненко, Олександр Миколайович; Chernenko, Oleksandr; Chernenko, O. M.; Chernenko, Oleksandr Mikolajovich; Chernenko, O.; Черненко, Олена Іванівна; Chernenko, O.; Chernenko, O. I.; Chernenko, Olena Ivanivna; Денисенко, Олена Григорівна; Олена, Григорівна (Дніпровський ДАЕУ, 2019)
Наведено результати досліджень впливу ознак будови тіла та молочну продуктивність, функцію відтворення та економічну ефективність експлуатації корів швіцької породи за дві лактації. Типи конституції корів визначали шляхом візуальної оцінки та за модальними відхиленнями індексів, які характеризують пропорції тулуба в ширину. Метою досліджень було встановити зв'язок між типами конституції та продуктивними ознаками корів. Установлена перевага ейрисомних над лептосомними тваринами за надоєм на 732 кг (Р>0,95), молочним жиром на 26 кг (Р>0,95) та молочним білком на 22,9 кг (Р>0,95) за 305 діб другої лактації. Пропонується за інших рівних умов з метою подальшого розвитку стада надавати перевагу коровам ейрисомного типу конституції. The results of research on the effects of body structure and milk production, reproduction and economic efficiency of Shvtsky breed cattle for two lactation are presented. The types of constitution of cows were determined by visual evaluation and modal deviations of indices that characterize the proportions of the trunk in width. The purpose of the research was to establish a link between the types of constitution and the productive features of cows. It was established that there was an advantage over leptosomal animals with a diet of 732 kg (P> 0,95), a milk fat of 26 kg (P> 0,95) and a milk protein of 22,9 kg (P> 0,95) for 305 days of the second lactation. It is offered on other equal terms for the purpose of further development of the herd to give preference to the cows of the etymological type of the constitution.
Economically useful traits shvitskyh cows eyrysomnoho leptosomnoho and types of constitution
Черненко Олександр Миколайович https://orcid.org/0000-0002-8829-3148 Черненко Олена Іванівна https://orcid.org/0000-0002-5951-6576
Keywords: економічна ефективність; economic efficiency; проміри екстер’єру; exterior dimensions; індекси екстер’єру; exterior indices; товщина шкіри; skin thickness; молочна продуктивність; milk productivity; відтворювальна здатність; reproductive capacity